Proceedings of the 2017 CHI Conference Extended Abstracts on Human Factors in Computing Systems 2017
DOI: 10.1145/3027063.3053126
|View full text |Cite
|
Sign up to set email alerts
|

On the Road with an Autonomous Passenger Shuttle

Abstract: The integration of autonomous vehicles (AVs) onto public roads presents both technical and social challenges. Public understanding and acceptance of AVs requires engagement with people who live in, work at or visit cities where they are deployed on public road networks. We investigate the impact of one of the first placements of AV passenger transport on public roadways: the Sion <>. This latebreaking research presents preliminary results from interviews with local shopkeepers, residents, pedestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 17 publications
0
23
0
3
Order By: Relevance
“…The categories that emerged from the data represent the factors influencing the acceptance of automated shuttles as feeders to transport systems. These categories were compared to theoretical concepts from the literature (e.g., Eden et al, 2017aEden et al, , 2017bMeijkamp & Theunissen, 1996;Nordhoff, De Winter, Kyriakidis, et al, 2018;Nordhoff, De Winter, Madigan, et al, 2018;Parasuraman, Zeithaml, & Berry, 1985, 1988Redman, Friman, Gärling, & Hartig, 2013;Vöge & McDonald, 2003).…”
Section: Interviewing Procedures and Analysismentioning
confidence: 99%
“…The categories that emerged from the data represent the factors influencing the acceptance of automated shuttles as feeders to transport systems. These categories were compared to theoretical concepts from the literature (e.g., Eden et al, 2017aEden et al, , 2017bMeijkamp & Theunissen, 1996;Nordhoff, De Winter, Kyriakidis, et al, 2018;Nordhoff, De Winter, Madigan, et al, 2018;Parasuraman, Zeithaml, & Berry, 1985, 1988Redman, Friman, Gärling, & Hartig, 2013;Vöge & McDonald, 2003).…”
Section: Interviewing Procedures and Analysismentioning
confidence: 99%
“…The Rise of Driverless Vehicles. Driverless vehicles are currently being developed in a number of commercial and research projects worldwide [1,2]. Shuttles that function as shared transport systems are a promising business case [3].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only few studies have been conducted that look into the future acceptance of autonomous buses [20,6]. Recent demonstration projects of autonomous buses have shown that passengers feel rather safe in automated buses [5], but, as noted by Rehrl et al [23] this is likely caused by the presence of a human operator, who is required by law during all drives.…”
Section: Introductionmentioning
confidence: 99%